Adverse Histologic Features in Colorectal Nonpedunculated Malignant Polyps With Nodal Metastasis. (February 2020) - Patel, Natalie; Vyas, Monika; Celli, Romulo; Jain, Dhanpat; Zhang, Xuchen
Abstract : Tumor differentiation, lymphovascular invasion, margin status, polyp shape, and size are important parameters of malignant polyps (pT1) indicating possible node metastasis, which justifies a surgery. However, the size, margin, and lymphovascular invasion are often unknown or difficult to assess in a piecemeal polypectomy from a nonpedunculated malignant polyp. The aim of the study was to identify adverse histologic features in nonpedunculated malignant polyps associated with an increased risk of nodal metastasis, which may warrant a colectomy procedure. A total of 24 node-positive and 18 node-negative nonpedunculated malignant polyps and their corresponding subsequent resection specimens from 2005 to 2018 were reviewed. Cases with node metastasis were more often positive for high-grade tumor budding (70.8% vs. 16.7%; P =0.0005), poorly differentiated clusters (54.2% vs. 22.2%; P =0.0369), and both high-grade tumor budding and poorly differentiated clusters (45.8% vs. 11.1%; P =0.0160) compared with controls without nodal metastasis. High-grade tumor budding, poorly differentiated clusters, and combined high-grade tumor budding and poorly differentiated clusters increased the risk of nodal metastasis, with odds ratio of 12.1, 4.1, and 14.3, respectively. Furthermore, nodal metastasis could be seen in subsequent colectomy specimen even in completely excised malignant polyps with adverse histologic features. Our findings indicate that high-grade tumor budding and poorly differentiated clusters are important adverse histologic risk features in predicting lymph node metastatic potential. These histologic features should be reported and it may warrant a colectomy when they are present.